SATU RUMAH SATU PANGAN LOKAL: INOVASI KETERSEDIAAN PANGAN KELUARGA DENGAN LABU MADU DI DESA SUKADIRI - Kiki Faisal; Farid Akbar Kusnadi; Alia Putri Nathania; Rafi Taziri; Julieta Rizka Andini; Tia Putri Maharani; Izzatul Alya; Frisky Friendly Jovial; Khaila Syasya Nabila; Dennis Lintang Octavianingrum; Dwi Lestari; Reysha Jihan Fazia (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Food availability at the family level is an important issue in strengthening national food security, especially in rural areas. In Sukadiri Village, the “One House One Local Food” Program offers an innovative solution by encouraging the use of honey pumpkin (Butternut squash) as a local food source that is highly nutritious and easy to cultivate. The choice of honey pumpkin is based on its high nutritional content and its ability to grow well in home yards, so that it can support the fulfillment of food needs while increasing family income. The implementation of this program includes education and assistance to residents regarding planting techniques, processing, and utilization of honey pumpkin as daily food. Preliminary results show an increase in community enthusiasm in cultivating honey pumpkin, a variety in food consumption, as well as a positive impact on improving family nutrition and strengthening the household economy. This innovation is also strengthened by the synergy between sectors, including the active involvement of agricultural extension workers and health workers in providing nutrition education and monitoring community development. Therefore, the one house one local food approach based on honey pumpkin has proven to be a strategic step towards family food independence and sustainability in Sukadiri Village. Keywords: Food Security, Honey Pumpkin, Local Food